Tacrolimus pharmacokinetics of once-versus twice-daily formulations in de novo kidney transplantation: a substudy of a randomized phase III trial - Włodarczyk, Zbigniew; Krämer, Bernhard (Therapeutic drug monitoring, 2012)
Background Tacrolimus is a well-established immunosuppressive agent for the treatment and prevention of solid organ graft rejection. It is available as an immediate-release, twice-daily formulation (Tacrolimus BID) and a prolonged-release, once-daily formulation (Tacrolimus QD). In a previous study of the pharmacokinetics (PK) of these formulations, mean systemic exposure [area under the curve from 0 to 24 hours (AUC0-24)] of tacrolimus on day 1 was approximately 30% lower for Tacrolimus QD than for Tacrolimus BID; by day 14, systemic exposure was similar; however, the mean dose of Tacrolimus QD was higher to achieve similar systemic exposure as Tacrolimus BID. Methods To further compare the PK of the tacrolimus formulations during the first 2 weeks posttransplant, a substudy was performed in a subset of patients enrolled into a phase III trial in de novo kidney transplant recipients comparing Tacrolimus QD and Tacrolimus BID. To minimize the difference in exposure observed in the earlier study, tacrolimus therapy was initiated before transplant. The PK analysis set comprised 34 patients (17 patients per treatment group) who had 4 complete PK profiles and no major PK-related protocol violations. Results Mean AUC0-24 of tacrolimus on day 1 was approximately 16% lower for Tacrolimus QD than for Tacrolimus BID, although by day 3 onward, the exposure was similar between treatment groups. Analysis of dose-normalized AUC0-24 (dose normalized to 0.1 mg/kg) showed a similar pattern. There was a good correlation between AUC0-24 and concentration of tacrolimus at 24 hours postdose for both formulations (Tacrolimus QD, r = 0.87; Tacrolimus BID, r = 0.92), and the slope of the line of best fit was similar. Conclusions These results suggest that initiating tacrolimus therapy before transplant reduces the difference in exposure between Tacrolimus QD and Tacrolimus BID.
Gesehen am 01.10.2018